Adapting the Canadian CT head rule age criteria for mild traumatic brain injury. Issue 10 (20th July 2019) - Fournier, Nicolas; Gariepy, Charles; Prévost, Jean-François; Belhumeur, Vincent; Fortier, Émile; Carmichael, Pierre-Hugues; Gariepy, Jean-Luc; Le Sage, Natalie; Émond, Marcel
Abstract : Objective: With the ageing population, the prevalence of mild traumatic brain injury (mTBI) among older patients is increasing, and the age criteria of the Canadian CT head rule (CCHR) is challenged by many emergency physicians. We modified the age criteria of the CCHR to evaluate its predictive capacity. Methods: We conducted a retrospective cohort study at a level 1 trauma centre ED of all mTBI patients 65 years old and over with an mTBI between 2010 and 2014. Main outcome was a clinically important brain injury (CIBI) reported on CT. The clinical and radiological data collection was standardised. Univariate analyses were performed to measure the predictive capacities of different age cut-offs at 70, 75 and 80 years old. Results: 104 confirmed mTBI were included; CT scan identified 32 (30.8%) CIBI. Sensitivity and specificity (95% CI) of the CCHR were 100% (89.1 to 100) and 4.2% (0.9 to 11.7) for a modified criteria of 70 years old; 100% (89.1 to 100) and 13.9% (6.9 to 24.1) for 75 years old; and 90.6% (75.0 to 98.0) and 23.6% (14.4 to 35.1) for 80 years old. Furthermore, modifying the age criteria to 75 years old showed a reduction of CT up to 25% (n=10/41) among the individuals aged 65–74 without missing CIBI. Conclusion: Adjusting the age criteria of the Canadian CT head rule to 75 years old could be safe while reducing radiation and ED resources. A future prospective study is suggested to confirm the proposed modification.